2011
DOI: 10.1111/j.1600-051x.2011.01770.x
|View full text |Cite
|
Sign up to set email alerts
|

Poor oral hygiene and gingivitis are associated with obesity and overweight status in paediatric subjects

Abstract: The gingivitis observed in overweight and obese young subjects is probably due to a combination of metabolic and inflammatory profiles and neglected attitude towards oral hygiene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
2
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 51 publications
5
66
2
7
Order By: Relevance
“…On the other hand, other findings verified a positive association between gingival inflammation and obesity in children and adolescents 20,25 . The study by Franchini et al 25 also showed a significant effect of obesity on children and adolescents, aged 10 to 17, and stressed that this association may be the result of a combination of metabolic inflammation and poor oral hygiene.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…On the other hand, other findings verified a positive association between gingival inflammation and obesity in children and adolescents 20,25 . The study by Franchini et al 25 also showed a significant effect of obesity on children and adolescents, aged 10 to 17, and stressed that this association may be the result of a combination of metabolic inflammation and poor oral hygiene.…”
Section: Discussionmentioning
confidence: 76%
“…The study by Franchini et al 25 also showed a significant effect of obesity on children and adolescents, aged 10 to 17, and stressed that this association may be the result of a combination of metabolic inflammation and poor oral hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…(2) the periodontitis in which the irritation and inflammation continues and results in tissue destruction and alveolar bone resorption. [39,38] In periodontal disease, destruction of the connective tissue for the most part, comes about because of the association of microscopic organisms (bacteria); their items & their products with mononuclear cells. [40,41,42] Α number of studies have shown that there is а wide range of systemic risk factors for periodontаl disease; these elements incorporate overweight/obesity, tobacco smoking, respiratory diseases, diabetes mellitus, rheumatoid arthritis, osteoporosis, cardiovascular disorders, kidney diseases, and dementia.…”
Section: Introductionmentioning
confidence: 99%
“…O acúmulo de placa bacteriana nas superfícies dentárias está associado com a presença de alterações bucais como a presença de sangramento gengival e de cálculo dentário, e consequentemente à doença periodontal (IRIGOYEN-CAMACHO et al, 2014;FRANCHINI et al, 2011). Os obesos avaliados neste estudo (G1 e G2) apresentaram pobres condições de higiene bucal na avaliação inicial (Tabela 4), dado que vai ao encontro do exposto na literatura científica (KIM et al, 2014;AKMAN et al, 2012;DE CASTILHOS et al, 2012;MATHUR et al, 2011;ZERMENO-IBARRA et al, 2010).…”
Section: Condições Periodontais E De Higiene Bucalunclassified